A survey of adjustable robust optimization - Yanıkoğlu, İhsan; Gorissen, Bram L.; den Hertog, Dick (European journal of operational research, 2019)
•Surveys the literature on applications of adjustable robust optimization.•Surveys theoretical and methodological aspects of adjustable robust optimization.•Guides practitioners on how to apply adjustable robust optimization methods.•Presents the advantages and limitations of the adjustable robust optimization. Static robust optimization (RO) is a methodology to solve mathematical optimization problems with uncertain data. The objective of static RO is to find solutions that are immune to all perturbations of the data in a so-called uncertainty set. RO is popular because it is a computationally tractable methodology and has a wide range of applications in practice. Adjustable robust optimization (ARO), on the other hand, is a branch of RO where some of the decision variables can be adjusted after some portion of the uncertain data reveals itself. ARO generally yields a better objective function value than that in static robust optimization because it gives rise to more flexible adjustable (or wait-and-see) decisions. Additionally, ARO also has many real life applications and is a computationally tractable methodology for many parameterized adjustable decision variables and uncertainty sets. This paper surveys the state-of-the-art literature on applications and theoretical/methodological aspects of ARO. Moreover, it provides a tutorial and a road map to guide researchers and practitioners on how to apply ARO methods, as well as, the advantages and limitations of the associated methods.